ANALISIS PERLINDUNGAN KONSUMEN DALAM PEREDARAN APPLE WATCH PALSU PADA TOKO E-COMMERCE DI INDONESIA - NIM. A1011221093, LUCKI ANANDA GULZARD (Jurnal Fatwa Hukum, 2025)
Abstract This research is motivated by the widespread circulation of counterfeit Apple Watches sold through e-commerce platforms in Indonesia, particularly Shopee. This practice is carried out using misleading strategies, such as the use of “100% original” labels, the use of official logos, and the utilization of promotional features, which ultimately cause losses to consumers. This condition illustrates a gap between the existing regulations and their implementation in the field. The purpose of this research is to analyze the implementation of legal regulations in protecting consumers against the circulation of counterfeit Apple Watches on e-commerce platforms and to examine the efforts made by consumers to defend their rights when harmed. This research uses a normative juridical method with a descriptive-analytical approach. The data were obtained through literature studies of statutory regulations, academic literature, and documentation in the form of consumer reviews and complaints on e-commerce platforms. The results of the research show that although the legal instruments related to consumer protection in Indonesia are adequate, such as Law Number 8 of 1999 on Consumer Protection covering Articles 4, 7, 8, 9, and 10; Law Number 1 of 2024 on Electronic Information and Transactions covering Article 28; Government Regulation Number 80 of 2019 on Electronic Commerce covering Article 34; and Ministry of Trade Regulation Number 50 of 2020 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Electronic Commerce covering Articles 18 and 19, their implementation remains weak. Many business actors ignore these provisions by displaying fake advertisements and misleading product information, while supervision from the e-commerce platform has not been optimal. On the other hand, consumers’ efforts to defend their rights, whether through internal application mechanisms or independent efforts, still face various obstacles, such as technical limitations and minimal responsiveness from business actors. The conclusion of this research is that consumer protection in e-commerce transactions has not yet been effective, leaving consumers in a weak position. Legal awareness from business actors, as well as enhanced supervision and enforcement of regulations by e-commerce platform providers and the government, is required. Keywords: Consumer Protection, E-commerce, Fake Apple Watch Abstrak Penelitian ini dilatarbelakangi oleh maraknya peredaran Apple Watch palsu yang dijual melalui platform e-commerce di Indonesia, khususnya Shopee. Praktik tersebut dilakukan dengan strategi yang menyesatkan, seperti penggunaan label “100% original”, pemakaian logo resmi, hingga pemanfaatan fitur promosi, yang pada akhirnya menimbulkan kerugian bagi konsumen. Kondisi ini menggambarkan adanya kesenjangan antara regulasi yang telah tersedia dengan implementasi di lapangan. Tujuan penelitian ini adalah untuk menganalisis implementasi regulasi hukum dalam melindungi konsumen terhadap peredaran Apple Watch palsu di e-commerce serta mengkaji upaya konsumen dalam mempertahankan haknya ketika dirugikan. Penelitian ini menggunakan metode yuridis normatif dengan sifat deskriptif analitis. Data yang diperoleh melalui studi kepustakaan terhadap peraturan perundang-undangan, literatur, serta dokumentasi berupa ulasan dan keluhan konsumen di platform e-commerce. Hasil penelitian menunjukkan bahwa meskipun perangkat hukum terkait perlindungan konsumen di Indonesia telah cukup, seperti Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen meliputi Pasal 4,7,8,9, dan 10, Undang-Undang Nomor 1Tahun 2024 tentang Informasi dan Transaksi Elektronik meliputi Pasal 28, Peraturan Pemerintah Nomor 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik meliputi pasal 34, serta Peraturan Menteri Perdagangan Nomor 50 Tahun 2020 tentang Ketentuan Perizinan Usaha, Periklanan, Pembinaan, dan Pengawasan Pelaku Usaha dalam Perdagangan Melalui Sistem Elektronik meliputi Pasal 18 dan 19. Namun, implementasinya masih lemah. Banyak pelaku usaha yang mengabaikan ketentuan tersebut dengan menampilkan iklan palsu dan informasi produk yang menyesatkan, sementara pengawasan dari pihak e-commerce belum optimal. Di sisi lain, upaya konsumen untuk mempertahankan haknya, baik melalui mekanisme internal aplikasi maupun upaya mandiri, masih menghadapi berbagai kendala, seperti keterbatasan teknis dan minimnya respons dari pelaku usaha. Kesimpulan penelitian ini adalah bahwa perlindungan konsumen dalam transaksi e-commerce masih belum berjalan efektif, sehingga konsumen tetap berada pada posisi lemah. Diperlukan kesadaran hukum dari pelaku usaha, serta peningkatan pengawasan dan penegakan regulasi oleh penyelenggara e-commerce dan pemerintah. Kata Kunci: Perlindungan Konsumen, E-commerce, Apple Watch Palsu